Legal Environmental Protection and Sustainable Development in the United Arab Emirates - Khater, Maya; Yassine Chami; Mohamad Albakjaji (Journal of Human Rights, Culture and Legal System, 2025)
Environmental protection and sustainability have captured global attention in recent years due to rising pollution, resource depletion, and climate change. In response to these challenges, this study examines how the United Arab Emirates (UAE) has developed its national environmental legislation in comparison with international legal frameworks. By applying a critical and comparative legal analysis, the study reviews key international environmental agreements and evaluates how UAE laws align with or diverge from global standards. The findings show that, first, the UAE has actively implemented forward-looking environmental policies through legislative reforms and sustainability initiatives aimed at meeting or exceeding international goals. Second, the UAE has promoted environmental responsibility by attracting clean technologies and fostering innovation, demonstrating its commitment to sustainable development. Third, despite these advancements, the study identifies continuing gaps in law enforcement and limited public participation in environmental decision-making processes. To address these issues, the study recommends enacting new legislation that includes constitutional protection of environmental rights and frameworks to strengthen regional environmental partnerships. The study also urges policymakers to encourage broader community engagement by empowering citizens and residents to participate in environmental policymaking and to file lawsuits against entities that violate environmental laws. This research contributes to the ongoing discourse on environmental governance by offering a legal analysis of the UAE’s evolving regulatory landscape and by proposing inclusive, enforceable approaches to environmental sustainability.